Current Situation of Meadow-Rangelands, Animal Existence and Cultivation for Forage Crops in Turkey, Eastern Anatolia Region and Muş Province - Mahir Özkurt; Selahattin Çınar (Turkish Journal of Agriculture: Food Science and Technology)
The most important way to reduce feed inputs is to increase the amount of good quality roughage. According to official data of Turkey Statistical Institute (TSI) in 2018, Turkey has 18.6 million bovine animal unit (BAU) livestock existence, and 85 million tons of quality roughage is needed to feed the animal existence. However, total quality roughage production of in the Turkey is 59 million, 10 million from meadow and grassland lands, 18 million from forage crops, 31 million from plant residues. Accordingly, the roughage gap in the country is 26 million tons, this accounts for 30% of the need. The quality roughage deficit is quite above this. The Eastern Anatolia region and Muş province have a great potential in Turkey’s animal husbandry both in terms of the presence of animals and the productivity of the grassland areas. The amount of forage crops produced in the region, where livestock is based on pasture and grassland in general, is also above the average of forage crops produced in Turkey. In order to closure roughage gap in Turkey, it is necessary to obtain higher yields from these areas by improvement and using them in accordance with the technique of those areas. In addition, it is necessary to increase the cultivation areas of forage crops within the field agriculture. By the closure of the shortage of roughage, higher animal production will be achieved, input costs may decrease, and the income level of animal producers will increase and the price of animal products may decrease. The research in Turkey, Eastern Anatolia Region and Mus Province of grassland and forage crops status, deficit and status of roughage, issues were analyzed.